Traditional Medicine Pattern for Self-Medication in Temajuk Village, a 3T (Frontier, Outermost, and Underdeveloped) Region in West Kalimantan - Muhammad Akib Yuswar; Eka Kartika Untari; Robiyanto Robiyanto (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Living in a 3T region (frontier, outermost, and underdeveloped) of West Kalimantan, people who live in Temajuk village, have long been practicing self-medication using traditional medicines. Despite the existence of a primary care service in Temajuk, the people’s habit in utilising natural herbal medicine to cure their illness still exists until now. The aim of this study was to identify patterns of traditional medicine as self-medication treatment among Temajuk villagers. This study was a cross sectional descriptive study using 138 participants who met the criteria including aged 20-50 years and have been practising self-medication. The participants were asked to fill a set of questionnaire. The results of this study showed that the average age of participants was 33.86 y.o. They used Piper betle folium mostly (39.86%) in self-medication practice. 44.2% of participants believed in traditional medicine. Fever (22.47%) was the most chosen indications to use traditional medicine for self-medication. 60.87% respondents used traditional plant from their back and 59.42% of them made it into decocta or infusum. Most of participants did not experience any adverse effect (86.96%) during self-medication practice. In brief, this study proved that the practice of self-medication using traditional medicine is often to occur and still important for people in Temajuk village.